2015
DOI: 10.4067/s0301-732x2015000100002
|View full text |Cite
|
Sign up to set email alerts
|

Is cryptosporidiosis an underestimated disease in cats?

Abstract: RESUMEN Estudios científicos acerca de la presencia de Cryptosporidium spp. en los gatos son escasos. En esta revisión bibliográfica se tratan los aspectos epidemiológicos y clínicos, así como los métodos de diagnóstico, la conducta terapéutica, y las medidas de control y prevención de la cryptosporidiosis en el gato doméstico, con el objetivo de establecer si se trata de una enfermedad subestimada en la rutina de laboratorio y en la clínica de pequeños animales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Cryptosporidium spp. is one of the most common intestinal parasites in cats, around the world prevalence rates have been reported, which can vary from 0 to 30% [11], furthermore, it has a high zoonotic transmission potential, that can cause chronic gastrointestinal diseases [12]. In this study, a high prevalence (51.9%) of Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 68%
“…Cryptosporidium spp. is one of the most common intestinal parasites in cats, around the world prevalence rates have been reported, which can vary from 0 to 30% [11], furthermore, it has a high zoonotic transmission potential, that can cause chronic gastrointestinal diseases [12]. In this study, a high prevalence (51.9%) of Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 68%
“…Among the positive isolate, C. parvum , C. felis , and mixed infection ( C. felis and muris ) were characterized. Some studies from elsewhere have confirmed the presence of Cryptosporidium in cats with prevalence ranging from 1 to 25% ( 17 19 ). Similar to our results, there are various reports in which detected Cryptosporidium species in cats.…”
Section: Discussionmentioning
confidence: 93%